Effect of Dietary Fishmeal on Cell-Mediated Immune Response of Laying Hens - Babu, U.S.; Wiesenfeld, P.L.; Raybourne, R.B.; Myers, M.J.; Gaines, D. (International Journal of Poultry Science, 2005)
In this study, we examined the role of different amounts of dietary fishmeal, a component of chicken diet on cell-mediated immune response of chickens. Forty eight laying white Leghorn chickens were randomly divided into 4 groups and fed diets containing 0, 1.5, 3 or 6% fish-meal. Six chickens from each dietary group were euthanized 3 and 9 weeks later and the spleens were removed to isolate cells and assess immune response. Mitogenic response was determined by 3H-thymidine incorporation and the cell subsets were established by flow cytometry. Three weeks of dietary treatment had no impact on Concanavalin A (Con A) or phytohemagglutinin (PHA) induced proliferation or cell subsets of splenic lymphocytes. However, 9 weeks post dietary treatment PHA-induced proliferation and CD4 cell population were elevated in 3% fishmeal fed hens compared to those fed the control (0% fishmeal) diet. Our results suggest that a moderate increase in dietary fish-meal may enhance the immune response in laying hens. This may prove useful in infections in which cell-mediated immunity plays a role.